PENGARUH STRATEGI KOMUNIKASI PEMASARAN BANK BJB DALAM CAMPAIGN “BJB CYCLING DIGICASH V-RIDE” TERHADAP PERILAKU ANGGOTA KOMUNITAS SEPEDA ROADBIKE - Rahiem, Vikry Abdullah (Ilmu Komunikasi, FISIP Universitas Pasundan, 2021)
Marketing communication comprises six primary communication methods: advertising, sales promotion, events and experiences, public relations and publicity, direct marketing, and personal selling. The expected effect of the marketing communication strategy through the bjb Cycling DigiCash V-Ride campaign is to serve as a stimulus that influences behavioral outcomes, specifically the behavior of cycling community members as potential customers (clients) of Bank BJB. This involves their decision to become Bank BJB clients who will regularly use the BJB DigiCash application for daily transactions, particularly for members of the cycling community